Species Composition and Catch Rate of Cast Net Fisheries in Kerinci Lake, Jambi - Ananda, Destha Dwi; Fatati; Magwa, Rizky Janatul; Yurleni; Yunita, Lauura Hermala; Putinur (Journal of Fish Health, 2025)
Capture fisheries in inland waters play a vital role in supporting food security and the economy of the community, including fishermen in Lake Kerinci who utilize cast nets as an economical and effective fishing gear. However, scientific information on catch composition, catch rates, and technical factors influencing the productivity of this gear is still limited. The purpose of this study was to analyze catch composition, catch rates, and factors influencing catch yields from cast nets in Lake Kerinci, Kerinci Regency, Jambi. The study was conducted from June 29 – August 7, 2025, using a survey method through participatory observation and interviews with 17 fishermen using cast nets, with a total of 34 data collection trips. Data collected included fish species, weight and number of catches, fishing duration, number of casts, and gear dimensions, then analyzed descriptively and using multiple linear regression. The results showed that the catch composition consisted of 162 tilapia (84.49% of the total weight) and 39 Nile tilapia (15.51%). The average catch rate of the throw nets reached 1.74 kg/hour, with the highest value for tilapia at 2.94 kg/hour. Regression analysis results showed that fishing duration, number of throws, and gear dimensions had no significant effect on catch results (p>0.05). It can be concluded that the throw nets in Lake Kerinci predominantly catch tilapia, while technical factors of the gear are not the main determinants of catch results. Environmental conditions and fish stock availability are suspected to have a greater influence on catch results.